INTENSI PERILAKU PENGGUNAAN E-LEARNING MENGGUNAKAN METODE TAM (TECHNOLOGY ACCEPTANCE MODEL) - Fatoni, Fatoni (JURNAL ILMIAH MATRIK, 2012)
This study aims to determine the factors that influence behavior intention Lecturers and students in the use of e-Learning. The method used to determine the factors that influence behavior intention towards e-learning system Bina Darma of University is to make use of methods of TAM (Technology Acceptance Model). In this study the variables that influence behavioral intention of using e-learning system consists of three variables, namely Perceived Usefulness (PU) and Perceived Ease of Use (PEOU) as independent variables while the behavioral intention of using e-Learning as a relevant variable. The results of this study indicate that both the independent variables PU and PEOU influencing variable associated with a value of 29.8% to 86.0% for students and faculty, while the rest is the influence of other factors. Keywords: E-Learning, System, TAM, PU, PEOU, Intention